Post-fordist affects, times and images: An ethnography of circulation in a digital advertising agency in Istanbul - Atıcı, Selim Gökçe. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This thesis follows the making and unmaking of commodity images, boundaries of embodied selves and emotional investments to work: cultivations regarding desiring and laboring, in relation to spatial-temporal dynamics between humans, things and affects. The discussion is set up against the backdrop of faster rates of commodity circulation, blurring boundaries between work and leisure and labor and play, and the augmentation (pervasiveness) of software, tools and possibilities of digital communication. It draws on my participant observation as a 'digital strategist' in a digital advertising company in Istanbul for four months. The Introduction defines several tensions that run throughout the thesis, which makes it more conceptual. In Chapter 2, I situate my ethnographic work in wider discussions on commodity fetishism and branding, attending to the practices of interpolation, tabulation and calculation as they reflect the making of novelty and fantasies of an automated society. Chapters 3 and 4 deal with the temporal self-understandings of digital media workers, and their relation to the workplace and the infrastructures of digital work. The final chapter plays with a working definition of 'genuineness' as an ambivalent affect that maps workplace authenticities and positions for self-fashioning in the workplace. The aim of this thesis is to situate digital/behavioral advertising work in a broader scale of global capitalism, informational networks, economic rationalities and space-time conundrums by engaging in dialogues with temporal self-understandings, affects and emotions, memory and anticipation, abstraction and embodiment, space and place, production and reproduction, and the ways in which working selves configure power relations.
Keywords: Digital media -- Turkey.; Digital media -- Social aspects.